Analysis of Shoreline Changes in the Coastal Area Between Batang Anai Estuary and Batang Mangur Estuary West Sumatra Province - Fairuzia, Putri Marwah; Rifardi, Rifardi; Siregar, Sofyan Husein (Journal of Coastal and Ocean Sciences, 2023)
This study aimed to determine the rate of change of the coastline and the effect of sedimentation processes, currents, and waves on the coastline in the coastal area between Batang Anai Estuary and Batang Mangur Estuary, West Sumatra Province. End Point Rate (EPR) is a method that can be used to calculate the rate of change of coastline by displaying transects according to their categories (high abrasion, medium abrasion, low abrasion, stable, and accretion). In 1993–2023, there was a change in the coastline in the form of abrasion, which reached ±150 m with a change rate of ±1.63 m/year. The abrasion at the research station is classified into high, medium, and low categories. Accretion also occurs in the area around the research station, and some areas do not experience significant changes or remain in a stable condition. Currents in the coastal area between Batang Anai Estuary and Batang Mangur Estuary, Padang Pariaman Regency, are included in the slow-moderate category with an average value of 0.19-0.28 m/s. Wave height is included in the low–low category with an average value of 0.1–0.58 m. Although currents and wave heights are included in the low category, some areas lacking coastal vegetation and no breakwaters can experience abrasion and accretion.